THE IMPLEMENTATION OF SCIENTIFIC APPROACH ON SPEAKING SKILL AT SMA NEGERI 18 MAKASSAR - Arruan, Ewin; Fansury , Andi Hamzah; Syam, Ulfah (Lembaga Jurnal FKIP Universitas Bosowa, 2024)
The aim of this research was to find out how the implement scientific approach to improve ability on speaking skill at SMA Negeri 18 Makassar. The method used in this research was quantitave experimental research with one group pre-test post-test research design. Speaking test was used as the instruments of collecting the data. The sample of this research were the second grade with 20 students. The result of data analysis showed that there was an enhancement speaking skills of fluency and pronunciation through the implementation scientific approach. The mean score of the students increased from 44.75 and the pre test to 76,25 on the post test. Based on the result of data analysis, the writer concludes that there was an enhancement after implementing the scientifict approach on speaking skill in second grade at SMA Negeri 18 Makassar.